2005
DOI: 10.4049/jimmunol.175.1.262
|View full text |Cite
|
Sign up to set email alerts
|

Dual Effects of p38 MAPK on TNF-Dependent Bronchoconstriction and TNF-Independent Neutrophil Recruitment in Lipopolysaccharide-Induced Acute Respiratory Distress Syndrome

Abstract: The administration of endotoxins from Gram-negative bacteria induces manifestations reminding of acute respiratory distress syndrome. p38 MAPKs have been implicated in this pathology. In this study, we show that the specific p38 α,β MAPK inhibitor, compound 37, prevents LPS-induced bronchoconstriction and neutrophil recruitment into the lungs and bronchoalveolar space in a dose-dependent manner in C57BL/6 mice. Furthermore, TNF induction and TNF signals were blocked. In TNF-deficient mice, bronchoconstriction,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
67
0
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 93 publications
(74 citation statements)
references
References 38 publications
4
67
0
3
Order By: Relevance
“…First, many of the protein pathways were redundant. For example, the p38 MAPK pathway has been implicated in the development of the exaggerated inflammation that is seen in ARDS (20). The network analysis showed that p38 MAPK may trigger part of its biological effect by increasing the expression of TNF-a, among other proteins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, many of the protein pathways were redundant. For example, the p38 MAPK pathway has been implicated in the development of the exaggerated inflammation that is seen in ARDS (20). The network analysis showed that p38 MAPK may trigger part of its biological effect by increasing the expression of TNF-a, among other proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that TNF-a, IL-1b, IL-6, and LBP are present in the BALF of patients with ARDS and contribute to the pro-inflammatory environment (16)(17)(18)(19)(20). In addition, p38 MAPK has also been shown to regulate key physiologic responses, including neutrophil recruitment and clearance of edema fluid, during the development of lung injury (20)(21)(22)(23). The proteins that were added into the network were predominantly cytokines, intracellular signaling proteins, and transcription factors that exist in extremely low concentrations in the BALF.…”
Section: Discussionmentioning
confidence: 99%
“…As mock control, WT mice were administered with saline. The airway function was evaluated by whole-body plethysmography [6]. Unrestrained conscious mice were placed in plethysmography chambers (EMKA Technologies, France), and Enhanced respiratory Pause (PenH), measured over 3-6 h. PenH can be conceptualized as the phase shift of the thoracic flow and the nasal flow curves indicating respiratory dysfunction pointing to airway resistance.…”
Section: Methodsmentioning
confidence: 99%
“…The lungs were fixed in 4% buffered formaldehyde for standard microscopic analysis, 3 mm sections were stained with haematoxylin and eosin (H&E) [62]. Neutrophil and erythrocyte accumulation in alveoli, disruption of alveolar septae and activation of alveolar epithelial cells were quantified using a semi-quantitative score with increasing severity of changes (0-5) as described previously [6,63]. Groups of 5-8 mice were included in each experiment and ten randomly selected high-power fields (400 Â magnifications) per animal were analyzed.…”
Section: Microscopy and Mpo Activity In Lungmentioning
confidence: 99%
See 1 more Smart Citation